Desain Pembelajaran PMRI Melalui Lesson Study pada Materi Menentukan Luas Permukaan Balok - Anna Fauziah; Ratu Ilma Indra Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to produce Student Worksheets 1 and 2 that use the Indonesian Realistic Mathematics Education approach on the material of surface area of ​​the beam that is valid, practical and has a potential effect on the teaching and learning process in the classroom. This study uses a design research method of development studies at the preliminary analysis and formative evaluation stages. In addition, lesson study is also used as a system used during design and implementation in the classroom. The research subjects were 25 students of the Palembang IBA Foundation Elementary School. The results showed that Student Worksheets 1 and 2 which had been designed using the context of wrapping paper were valid, practical and had a potential effect on the learning process in the classroom. In conclusion, the use of Indonesian Realistic Mathematics Education and lesson study at the time of implementation in the form of Student Worksheets with the context of wrapping paper in the classroom has helped students understand the concept of surface area of ​​a block, be able to solve problems and make learning more meaningful. Keywords: PMRI, Design Research, Lesson Study